AUDIT TATA KELOLA SISTEM INFORMASI PENDAFTARAN SISWA MENGGUNAKAN COBIT 4.1 DI BLK SURAKARTA - Haqiqi, Arif Naofal; Remawati, Dwi; Harsadi, Paulus (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
The registration information system at the BLK Surakarta enables data redundancy. It will be analyzed to avoid this. The process of registering student services into the system is limited to the number of prospective students but input data is still unable to implement policies so that when data input still occurs or data from the same data or many data often occur.           This study uses Cobit 4.1 to audit the registration information system available at the BLK Surakarta. The selected subdomain is the Delivery Subdomain and Support DS 10 and DS11, the purpose of which is to determine the maturity level value in the IT process that has been applied in the BLK Surakarta and provide recommendations that need to be corrected. Based on the maturity level statement in the Maturity Management Guidelines Control Framework.  The resulting output is the study indicate that BLK Surakarta must conduct system performance evaluations that are routinely carried out with those responsible for identifying and tracking problems so that they are aware of the current system conditions. In Domain 10 of Delivery & Support, the results of the Current Maturity Level calculation are 3.27 with conditions Determining the Process. While Domain Deliver & Support 11, the result of calculation of Current Maturity Level is 3.31 with the Requirements for Determining the Process. The new student registration section has implemented a payment data management process but the lack of available tools makes data management less than optimal.Keywords: Student Registration Services, Registration Information System, COBIT 4.1, DS 10  and DS11 Domains, Defined Process